Hydrogen Crossover in PEM and Alkaline Water Electrolysis: Mechanisms, Direct Comparison and Mitigation Strategies. Issue 7 (1st January 2018) - Trinke, P.; Haug, P.; Brauns, J.; Bensmann, B.; Hanke-Rauschenbach, R.; Turek, T.
Abstract : This study provides a direct comparison of hydrogen crossover in PEM (Nafion 117) and alkaline water electrolysis (Zirfon) at a temperature of 60 ∘ C applying state-of-the-art separating unit materials. To this end, occurring crossover mechanisms are described first, before experimental data of the anodic hydrogen content are shown in dependence of current density, system pressure and process management strategy. The results suggest that permeation in PEM electrolyzers is mainly governed by diffusion due to a supersaturated concentration of dissolved hydrogen within the catalyst layer, showing a share of 98